Karakteristik Pasien Tersangka Apendisitis Tahun 2021-2023 di Rumah Sakit Ibnu Sina Makassar - Wulandari, Rezky Dwi; Syahril, Erlin; Nulanda, Mona; Purnamasari, Renny; Rahmawati, Rahmawati (Yayasan Citra Cendekia Celebes, 2025)
Appendicitis is an inflammation that occurs in the vermicular appendix. This disease is the most common inflammation found in all ages and genders. The prevalence of appendicitis in Indonesia in 2019-2020 was 3,326 and 596,132. Indonesia was ranked 4th in 2018 with 28,040 hospitalized patients. Anamnesis and physical examination play a major role, radiological and laboratory examinations help find differential diagnoses or results whose diagnosis is still in doubt. Objective: What are the characteristics of patients suspected of appendicitis in 2021-2023 at Ibnu Sina Hospital Makassar. Method: Design of this research is descriptive using a retrospective method. Results: Gender 50% male and 50% female. Age 15-24 (46.15%), less than 15 years (15.38%), 25-44 years (19.23%), 45-54 years (11.53%) and more than 54 years (7.26%), (100%) patients with lower right abdominal pain, nausea (65.4%), vomiting (61.5%), fever (42.3%), weakness (26.9%), heartburn and decreased appetite (7.7%). (46.2%) patients with normal leukocytes, (53.8%) increased leukocytes. USG (57.7%) impression of appendicitis, (42.3%) normal, (15.4%) other diseases. Pathological anatomy (30.8%) chronic appendicitis (26.9%) acute appendicitis, and (42.3%) no pathological anatomy examination. Conclusion: Characteristics of patients suspected of appendicitis at the Hospital. Ibnu Sina Makassar 2021-2023 showed a balanced number between men and women with the most frequently diagnosed age group being 15-24 years with the main symptoms being lower right abdominal pain accompanied by increased leukocytes, there was also a match between the diagnosis of appendicitis and the results of the USG examination (57.7%) and the results of the most anatomical pathology examinations were chronic conditions with acute exacerbations.